Kontribusi Kepemimpinan Transformasional Kepala Sekolah dalam Meningkatkan Motivasi Kerja Guru (Sekolah Tinggi Ilmu Tarbiyah (STIT) Lingga, 2023)
This study aims to reveal how transformational leadership contributes to increasing teacher motivation. This study uses the method of literature study. In this literature study research, there are several criteria as follows: 1) The literature study discusses its relation to the principal's leadership contribution in increasing the work motivation of teachers in elementary schools; 2) Articles published within 10 years from 2012-2022; 3) Literature studies are the results of empirical research, not the results of literature studies; 4) Literature sources are taken from online databases which can be accessed free of charge through science direct, google scholar, and open knowledge maps; 5) The literature search keywords used as sources are transformational leadership and teacher work motivation. The results of the study show that the principal's transformational leadership contributes greatly to increasing the work motivation of teachers in elementary schools. There are 4 dimensions of transformational leadership of school principals that contribute to increasing teacher work motivation which include: Idealized Influence, Individualized consideration, Intellectual stimulation, and Inspirational motivation. Thus, the better the principal's transformational leadership, the higher the overall teacher's work motivation.